2018
DOI: 10.1016/j.humpath.2018.05.018
|View full text |Cite
|
Sign up to set email alerts
|

In situ analysis of mTORC1/2 and cellular metabolism–related proteins in human Lymphangioleiomyomatosis

Abstract: Lymphangioleiomyomatosis (LAM) is a rare progressive cystic lung disease with features of a low-grade neoplasm. It is primarily caused by mutations in TSC1 or TSC2 genes. Sirolimus, an inhibitor of mTOR complex 1 (mTORC1), slows down disease progression in some, but not all patients. Hitherto, other potential therapeutic targets such as mTOR complex 2 (mTORC2) and various metabolic pathways have not been investigated in human LAM tissues. The aim of this study was to assess activities of mTORC1, mTORC2 and var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Interestingly, 6 somatic mutations in the RICTOR gene were identified in 6 S-LAM patients separately in this study and somatic RICTOR mutations related to stomach and intestine cancers were documented in the COSMIC database. The RICTOR (rapamycin-insensitive companion of mTOR) gene encodes a core component of the mTOR complex-2 (mTORC2) and recent findings suggested that high mTORC2 activity may play a role in the pathogenesis of LAM [10,30]. Apparently, the functional significance of these RICTOR mutations need further investigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, 6 somatic mutations in the RICTOR gene were identified in 6 S-LAM patients separately in this study and somatic RICTOR mutations related to stomach and intestine cancers were documented in the COSMIC database. The RICTOR (rapamycin-insensitive companion of mTOR) gene encodes a core component of the mTOR complex-2 (mTORC2) and recent findings suggested that high mTORC2 activity may play a role in the pathogenesis of LAM [10,30]. Apparently, the functional significance of these RICTOR mutations need further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…LAM is known to be caused by mutations in the tuberous sclerosis complex (TSC) genes, TSC1 located on chromosome 9q34 encoding hamartin or TSC2 located on chromosome 16p13 encoding tuberin [810]. Mutations in both hamartin and tuberin lead to inactivation of the tuberin-hamartin complex, resulting in increased activity of a kinase known as the mammalian target of rapamycin (mTOR) leading to abnormal proliferation of smooth muscle-like cells (LAM cells), the underlying causes of a variety of pathological findings.…”
Section: Introductionmentioning
confidence: 99%
“…In case of disagreement over scoring, a third observer was also involved in the evaluation. An H-score (range: 0–300) was calculated by multiplying the staining intensity (0–3+) by the percentage of positive cells for each intensity [ 60 ]. We defined staining patterns as heterogeneous in those cases, where tumour cells were labelled with three different staining intensities simultaneously (+, ++ and +++); additionally, none of the intensity percentages reached 50% in the investigated specimens.…”
Section: Methodsmentioning
confidence: 99%
“…The mTORC1 is often deregulated in numerous cancer types, such as breast, cervical cancer, esophageal squamous cell carcinoma, lung and hepatic cancers (35)(36)(37)(38)(39). mTORC1 is often activated by mutations in its upstream regulators.…”
Section: Regulation Of Mtorc1 Signaling In Cancermentioning
confidence: 99%